Serous retinal detachment in patients with macular edema secondary to branch retinal vein occlusion - Celık,Erkan (2016)
ABSTRACT Purpose: The aim of the present study was to evaluate visual acuity (VA) and central macular thickness (CMT) to assess the influence of serous retinal detachment (SRD) in eyes with macular edema (ME) secondary to branch retinal vein occlusion (BRVO). Methods: Sixty-one eyes with BRVO from 61 patients with ME were analyzed and divided into two groups according to the spectral domain optical coherence tomography (OCT) findings of SRD and cystoid macular edema (CME). All patients underwent complete ophthalmic examinations and OCT measurements (Cirrus, Carl Zeiss Meditec Inc, Dublin, CA). Patients with marked retinal hemorrhage, diabetic retinopathy, previous laser photocoagulation, and/or intravitreal injection were excluded. Results: The mean age of included patients (37 males, 24 females) was 65.4 ± 11.4 (53-77) years. There were 21 patients with SRD and 40 patients with CME. All of the 21 patients with SRD had CME. VA was significantly worse in the SRD group compared with the CME (non-SRD) group (0.82 ± 0.34 logMAR vs 0.64 ± 0.38 logMAR; P=0.005). Conversely, CMT was significantly greater in the SRD group than in the CME group (465 ± 115 µ vs 387 ± 85 µ; P=0.00004). Conclusion: SRD may be associated with decreased VA. The prognosis of patients with BRVO and SRD requires further investigation.